The nationality issue in the Gdańsk Province in 1945–1947 - Hejger, Maciej (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes nationality issues in the Gdańsk Voivodeship during the first years following the Second World War, when the newly established Polish authorities faced the challenge of organizing an exceptionally complex ethnic structure. The aim of the study is to present the ethnic composition of the voivodeship, describe state policies toward various population groups, and assess the assumptions underlying efforts to create a homogeneous nation-state. The author employs a historical method based on administrative documents, provincial reports, and archival materials. The research demonstrates that the Gdańsk Voivodeship encompassed territories with diverse historical and ethnic backgrounds, resulting in a particularly complex nationality situation. Germans constituted the largest group, while Kashubians and Kociewians also formed a significant proportion of the population, alongside smaller groups of Russians, Belarusians, Ukrainians, Lithuanians, Latvians, Estonians, Tatars, Jews, Karaims, and Roma. The author argues that the authorities’ overriding objective was the national homogenization of the region through the expulsion of the German population and the assimilation or control of other ethnic groups. A particularly important issue was the status of the indigenous population, which on the one hand served as evidence of the region’s Polish character, while on the other hand was frequently viewed with suspicion by both the administration and incoming settlers. The conclusions indicate that nationality policy in the Gdańsk Voivodeship was subordinated to the idea of constructing a monoethnic nation-state. Its implementation encountered numerous difficulties arising from the region’s ethnic diversity and from contradictions between political objectives and social realities.